Regulation of the cystic fibrosis transmembrane conductance regulator anion channel by tyrosine phosphorylation. Issue 9 (10th June 2015) - Billet, Arnaud; Jia, Yanlin; Jensen, Tim; Riordan, John R.; Hanrahan, John W.
ABSTRACT: The cystic fibrosis transmembrane conductance regulator (CFTR) channel is activated by PKA phosphorylation of a regulatory domain that interacts dynamically with multiple CFTR domains and with other proteins. The large number of consensus sequences for phosphorylation by PKA has naturally focused most attention on regulation by this kinase. We report here that human CFTR is also phosphorylated by the tyrosine kinases p60c‐Src (proto‐oncogene tyrosine‐protein kinase) and the proline‐rich tyrosine kinase 2 (Pyk2), and they can also cause robust activation of quiescent CFTR channels. In excised patch‐clamp experiments, CFTR activity during exposure to Src or Pyk2 reached 80% of that stimulated by PKA. Exposure to PKA after Src or Pyk2 caused a further increase to the level induced by PKA alone, implying a common limiting step. Channels became spontaneously active when v‐Src or the catalytic domain of Pyk2 was coexpressed with CFTR and were further stimulated by the tyrosine phosphatase inhibitor dephostatin. Exogenous Src also activated 15SA‐CFTR, a variant that lacks 15 potential PKA sites and has little response to PKA. PKA‐independent activation by tyrosine phosphorylation has implications for the mechanism of regulation by the R domain and for the physiologic functions of CFTR.—Billet, A., Jia, Y., Jensen, T., Riordan, J. R., Hanrahan, J. W. Regulation of the cystic fibrosis transmembrane conductance regulator anion channel by tyrosine phosphorylation. FASEB J. 29, 3945‐3953 (2015). www.fasebj.org